Urbane Strukturen und bürgerliche Identität im Hellenismus - Matthaei, Albrecht; Zimmermann, Martin (Die hellenistische Polis als Lebensform, 2015)
This volume sums up the results of the special research program funded by the DFG, "The Hellenistic city as life form" (2006-2012). Accounts of the projects involved in this program document the vitality of daily life in Hellenistic cities. The decline of the classical polis did not shape this time, as was long thought. On the contrary, this time was characterized by dynamic processes of transformation, clear evidence that the polis was in fact flourishing both as a political institution and as an urban organization. The development of city space and architecture, as well as in political, legal, religious, and social life demonstrates the diverse, innovative, and trendsetting Hellenist practice in politics and urban design. Cities are considered in this work along with their settlement space and the surrounding landscape in which the majority of the inhabitants of the polis lived and worked. This volume is intended to serve as the basis for further research, exploring local and regional differences in more detail